2021
DOI: 10.1111/nmo.14184
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of high‐resolution esophageal manometry in children without dysphagia

Abstract: Background The absence of high‐resolution esophageal manometry (HREM) norms in pediatrics limits the assessment of children with dysphagia. This study aimed to describe HREM parameters in a cohort of children without dysphagia. Methods Children ages 9–16 years with a negative Mayo Dysphagia Questionnaire screen and normal histologic findings underwent HREM after completion of esophagogastroduodenoscopy. Ten swallows of 5 ml 0.45% saline boluses per subject were captured in supine position. Analyzed data includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For pediatrics normal values, we have used a previously published data. [6][7][8] Bolus transit was assessed using the impedance contour traces to visualize where the bolus remained in the esophageal body either post-peristalsis where present, or post-lower esophageal sphincter (LES) closure where peristalsis failed. IBC was defined as bolus (liquid or solid) entry without bolus clearance at any of the impedance recording sites and is divided into upper, lower and whole failure, dependent on area of incomplete clearance within the esophageal body.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For pediatrics normal values, we have used a previously published data. [6][7][8] Bolus transit was assessed using the impedance contour traces to visualize where the bolus remained in the esophageal body either post-peristalsis where present, or post-lower esophageal sphincter (LES) closure where peristalsis failed. IBC was defined as bolus (liquid or solid) entry without bolus clearance at any of the impedance recording sites and is divided into upper, lower and whole failure, dependent on area of incomplete clearance within the esophageal body.…”
Section: Methodsmentioning
confidence: 99%
“…4 Normal values and result interpretation in adults are based on plethora of evidence 5 but normative values in pediatric HRM are often based on small cohort studies. [6][7][8] In one pediatric study, all children with repaired EA were reported to have had an abnormal HRM findings. 9 Impaired motility can lead to abnormal transit in the esophageal body and/or incomplete bolus clearance (IBC).…”
Section: Introductionmentioning
confidence: 99%
“…However, in children younger than 2 years, a swallow study can be performed 3 . Normal manometry biometrics are available for 9-16-year-old patients 4 . A normal 5 th -95 th percentile range was published for children <18 years of age 5 .…”
Section: Hrem and Agementioning
confidence: 99%
“…Research on pediatric esophagus physiology can inform diagnostic criteria and treatment recommendations tailored to children. Interpretation of manometric data in children currently utilizes parameters derived from adult population [24 ▪ ,25]…”
Section: Future Directions For Chicago Classification Enhancementmentioning
confidence: 99%